Stabilization Policy with Bands - Gros, Daniel (IMF Working Papers; Working Paper ;, 1990)
This paper discusses stabilization policy in the presence of bands for the exchange rate. The bands are modelled in a probabilistic sense: monetary policy has to be such as to keep the probability, that the exchange rate stays within the bands, above a certain threshold. In contrast to other models of target zones, this formulation leads to a linear decision rule and implies sizeable intra-marginal interventions, which corresponds to the experience in the EMS. The extent to which short-run monetary policy is constraint by the bands depends on its own long-run components and on fiscal policy.